ABDUCTIVE REASONING SKILLS: THE IMPACT OF COOPERATIVE LEARNING TYPE NUMBER HEAD TOGETHER (NHT) ASSISTED BY LUMI EDUCATION IN SCIENCE LEARNING - Dania Yuliyati; Azzah Rohadatul Aisy; Sisilia Eka Maulidiah; Laily Rosdiana (Universitas Labuhanbatu, 2026)
Purpose – This study aims to determine the effectiveness of NHT Cooperative Learning assisted by Lumi Education in improving the abductive reasoning skills of junior high school students in science lessons on substance pressure material.Methodology – The research used a pre-experimental pretest with a replication across two schools. The effectiveness of learning in improving abductive reasoning skills was analyzed using pretest and posttest results. Data collection uses test and questionnaire methods. The test data were analyzed using the n-Gain score and the average difference test, while the response questionnaire data were analyzed using the Likert scale.Findings – The results of this study showed an n-Gain score of 0.71, indicating a high category. The results of the paired t-test showed a p-value of <0.001 (<0.05), indicating a significant difference in ability before and after the learning application. The results of the response questionnaire showed that 100% of students responded positively to learning. Thus, the implementation of NHT Cooperative Learning, assisted by Lumi Education, has proven effective in improving abductive thinking skills in science learning.Contribution – Abductive reasoning in science learning supports the scientific process so that students are able to design innovative solutions based on incomplete data. This research can serve as a basis for improving higher-order thinking skills so that students gain a deep, meaningful understanding and, in addition, can create an active classroom atmosphere and integrate technology into learning.